Examining the mathematics education values of diverse groups of students - Hill JL; Hunter J (Taylor and Francis Group, 2023)
In recent years, there has been increasing interest in examining values in relation to mathematics education research. Our exploratory study examines the mathematics education values of culturally diverse middle school students in New Zealand. We investigated how student values differed across demographic variables including school, ethnicity, gender and grades. Students completed an online survey to indicate the importance of 14 different mathematics education values. The overall mean ratings for each of the 14 values determined the relative value importance across the sample. One-way ANOVA assessed demographic group differences. Findings showed that respect was rated as the most important value across all student groups. Students from Pacific nations placed significantly greater importance on accuracy, communication, family and recall compared to the other ethnicities. Female students emphasized family, practice, respect, risk-taking and utility more than males. We argue that to provide equitable mathematics classrooms that support wellbeing, we need to recognize what diverse student groups value and then transform pedagogy to align with and build from students’ values. This article provides a contribution by offering a way of understanding and highlighting similarities and differences in student values which impact on students’ learning experiences and wellbeing.
Keywords: Affect; mathematics education values; equity; culture; well-being; wellbeing; engagement; respect